Pathogenic activity of Isaria spp. for control of Dactylopius opuntiae (Hemiptera: Dactylopiideae) and the effects of selected insecticides - Da Silva Lopes, Rosineide; Gonçalves De Oliveira, Luciana; De Lima, Geiziquele; Dos Santos Correia, Maria Tereza; Da Costa, Antonio Félix; De Luna-Alves Lima, Elza Áurea; De Menezes Lima, Vera Lúcia (Instituto de Ecología, A.C., 2019)
We analyzed the activity of the entomopathogenic fungi Isaria farinosa, I. fumosorosea and I. javanica against the cochineal Dactylopius opuntiae, as well as the effects of the insecticides clorpirifos, acetamiprid, thiamethoxam and lambda-cyhalothrin on the conidia germination, mycelium growth and a sporulation of the fungi. These fungi were not pathogenic to cochineal. This the first report of the efficiency of Isaria spp. against this the insect. The bioassays of the compatibility of the insecticides acetamiprid and thiametoxam with species of Isaria indicate the possibility of the joint use of these products in studies on the control of D. opuntiae.